2021
DOI: 10.4111/icu.20190248
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle strength is correlated with sexual function

Abstract: Purpose Sexual performance is related to proprioception and pelvic floor muscle strength (PFMS). The aim of this study was to correlate sexual activity and orgasm with PFMS. Materials and Methods A total of 140 healthy continent female were prospectively distributed into 4 groups according to age: Group 1 (G1), 30–40; Group 2 (G2), 41–50; Group 3 (G3), 51–60; Group 4 (G4), over 60 years old. Evaluated parameters were: frequency of sexual activity and orgasm achievement;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The vast majority of the nulliparae in our study were in their first trimester at the age of 30.18 years with a median MOS of 4 (2)(3)(4). It is generally anticipated that young women in an early stage of pregnancy have not experienced delivery and should have normal PFMS.…”
Section: Discussionmentioning
confidence: 85%
“…The vast majority of the nulliparae in our study were in their first trimester at the age of 30.18 years with a median MOS of 4 (2)(3)(4). It is generally anticipated that young women in an early stage of pregnancy have not experienced delivery and should have normal PFMS.…”
Section: Discussionmentioning
confidence: 85%
“…Some sociodemographic characteristics may have an effect on PFM strength. Some studies have reported that aging may lead to a decrease in mechanical strength and predispose an individual to prolapse, UI and sexual dysfunction [ 29 32 ]. Likewise, in our study, the PFM rapid, tonic, and endurance contraction amplitudes all decreased when age increased.…”
Section: Discussionmentioning
confidence: 99%
“…Weakened PFM is closely related to SUI, fecal incontinence, POP, and sexual dysfunction [ 5 , 21 ]. Additionally, women’s quality of life and ability to engage in everyday activities may be negatively affected by PFM strength [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Martinez et al [ 22 ] recruited 49 women to be interviewed for the Female Sexual Function Index questionnaire (FSFI) and graded for PFM strength, and concluded that women with stronger PFM were scored higher in the orgasm, sexual excitement, desire, and general questions on the questionnaire. Likewise, Sartori et al [ 21 ] recruited 140 healthy females to evaluate the frequency of orgasm achievable sexual activities to objectively evaluate PFM strength, and found that better PFM was correlated with better sexual function, suggesting that strengthening PFM is hopefully resulting in improving women’s quality of life.…”
Section: Discussionmentioning
confidence: 99%